First report of blaOXA-48 producing Klebsiella pneumoniae isolates from wastewater in Morocco - Amine Aiddi; Ilham Zerdani; Aboubakr Khazaz; Ihssane Benzaarate; Hafsa Mguild; Fatna Bourjilat; Kaotar Nayme (Journal of Public Health in Africa)
No abstract available.